Data analysis model selection for estimating local population size of the Risso’s dolphin (Grampus griseus) in the Azores - Stap, Tim Van der (2013)
Different models estimating cetacean population size require making assumptions about the marking and recapturing of individuals, and on the structure of the population. Crucial in selecting the most appropriate model is a critical assessment of these assumptions. In this study we applied the robust parameterization of the open Jolly-Seber (JS) model (POPAN), using the software program MARK. This model was applied to data collected on the Risso’s dolphin (Grampus griseus). Between 2004 – 2007, photo-identification was used as a Capture-Mark-Recapture technique to identify 670 unique individuals off Pico Island, Azores. For this model, it was assessed what assumptions are supported or violated. The aim of this study was improving our understanding of how to select the most appropriate population size model.